2021
DOI: 10.1039/d1cc04916j
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation and stabilisation of glycosylated enzymes on boronic acid-functionalised silica nanoparticles

Abstract: We report a method of glycosylated enzyme immobilisation and stabilisation based on the formation of boronate esters between a surface-attached boronate and the enzyme glycans, followed by the growth of an organosilica layer of controlled thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[27][28][29][30][31] In this context, we have focused our efforts on the supramolecular engineering of enzymes immobilised on the surface of silica and shielded in organosilica layers of controlled thickness and chemical composition. [32][33][34][35][36] Among enzymes of interest for industrial applications, cold active enzymes (CAEs) are of particular signicance as they exhibit catalytic activity at low temperatures. [37][38][39] Produced by psychrophiles, CAEs typically display a relatively high conformational mobility at the active site, which allows reducing the free energy of activation required to convert the substrate to the corresponding transition state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] In this context, we have focused our efforts on the supramolecular engineering of enzymes immobilised on the surface of silica and shielded in organosilica layers of controlled thickness and chemical composition. [32][33][34][35][36] Among enzymes of interest for industrial applications, cold active enzymes (CAEs) are of particular signicance as they exhibit catalytic activity at low temperatures. [37][38][39] Produced by psychrophiles, CAEs typically display a relatively high conformational mobility at the active site, which allows reducing the free energy of activation required to convert the substrate to the corresponding transition state.…”
Section: Introductionmentioning
confidence: 99%
“…27–31 In this context, we have focused our efforts on the supramolecular engineering of enzymes immobilised on the surface of silica and shielded in organosilica layers of controlled thickness and chemical composition. 32–36…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, a number of different methods for the immobilization of enzymes on solid surfaces have been developed, as summarized in many review articles. A recent focus is on the immobilization of enzymes for flow-through applications. , Conceptually, the methods for enzyme immobilization on silica surfaces can be grouped into at least three categories: (i) covalent binding to a silica surface using organic linker moieties and a chemical modification of the silica surface, , (ii) noncovalent adsorption on either neat silica or surface-modified silica, , and (iii) entrapment in the pores of porous silica materials. ,, For the methods based on noncovalent enzyme adsorption, three approaches are relevant for comparison to the work presented: (i) layer-by-layer deposition using a charged polymer that has an opposite charge to the overall charge of the enzyme at the pH applied, , (ii) the use of recombinant enzymes carrying His-tags to bind to a silica surface that is surface-functionalized to allow the efficient binding of His, and (iii) the use of recombinant chimeric enzymes containing a polycationic protein module (an arginine-rich mini protein) that binds to unmodified, anionic silica surfaces (“fusion protein approach”). ,, The methodology used in this work is somewhat related to the fusion protein approach, although the use of recombinant enzymes is not required. In our work, the enzyme of interest is immobilized noncovalently on unmodified silica surfaces after several enzyme molecules are first covalently bound to polymer molecules in an aqueous solution. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that immobilization of enzymes can improve enzyme performance. 10,11 Semiconductor quantum dots (QDs) have been attracting worldwide attention for their broad excitation spectra, adjustable emission peaks and high quantum yields (QYs). 12, 13 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are usually used to prepare protein-QD bioconjugates by coupling of -NH 2 in GOx and -COOH in QDs.…”
Section: Introductionmentioning
confidence: 99%